2016
DOI: 10.1002/uog.15898
|View full text |Cite
|
Sign up to set email alerts
|

Strategies for improving outcome of assisted reproduction in women with polycystic ovary syndrome: systematic review and meta‐analysis

Abstract: Objectives To identify, appraise and summarize the current evidence regarding the efficacy of strategies aimed at improving assisted reproductive techniques in women with polycystic ovary syndrome (PCOS). Methods (RR, 0.54 (95% CI,) and antagonist protocols compared with agonist protocols (RR, 0.63 (95% CI,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
27
0
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(35 citation statements)
references
References 101 publications
3
27
0
5
Order By: Relevance
“…At present, metformin therapy in PCOS during pregnancy is considered experimental and metformin during pregnancy in PCOS is not yet generally recommended. A recent meta-analysis found that metformin improved live birth/ongoing pregnancy (RR, 1.28 (95% CI, 1.01-1.63)) and clinical pregnancy rates (RR, 1.26 (95% CI, 1.04-1.53)) when compared with placebo or no intervention (106), but the studies were of low quality and the effect of metformin was only modest. A randomized controlled trial in pregnant women with PCOS, comparing metformin to placebo, reported no significant difference in GDM prevalence 17.6% and 16.9%, respectively (107); however, the study could have been underpowered to detect change in GDM prevalence.…”
Section: Metformin During Pregnancy In Pcosmentioning
confidence: 99%
“…At present, metformin therapy in PCOS during pregnancy is considered experimental and metformin during pregnancy in PCOS is not yet generally recommended. A recent meta-analysis found that metformin improved live birth/ongoing pregnancy (RR, 1.28 (95% CI, 1.01-1.63)) and clinical pregnancy rates (RR, 1.26 (95% CI, 1.04-1.53)) when compared with placebo or no intervention (106), but the studies were of low quality and the effect of metformin was only modest. A randomized controlled trial in pregnant women with PCOS, comparing metformin to placebo, reported no significant difference in GDM prevalence 17.6% and 16.9%, respectively (107); however, the study could have been underpowered to detect change in GDM prevalence.…”
Section: Metformin During Pregnancy In Pcosmentioning
confidence: 99%
“…The systematic review conducted by Kollmann et al 22 had different conclusions than the majority. They included 66 studies in their review of current evidence regarding the efficacy of strategies aimed at improving assisted reproductive techniques in women with PCOS, and measured the primary outcomes of live birth/ongoing pregnancy and ovarian hyper stimulation syndrome.…”
Section: Findings Metformin Use In Pcosmentioning
confidence: 95%
“…They concluded that there is low-quality evidence pointing to a benefit of metformin supplementation on clinical pregnancy and live birth rates. 22 Lastly, Sohrevardi et al 23 attempted to determine the effect of metformin and pioglitazone on clinical, hormonal and metabolic parameters in women with PCOS. They concluded that insulinsensitizing drugs induce beneficial effects in insulin resistance and menstrual cycle, but only metformin aided in reducing hyperandrogenemia in women with PCOS.…”
Section: Findings Metformin Use In Pcosmentioning
confidence: 99%
“…The most important problem is that fertility treatment is expensive, not being affordable for the majority of couples, particularly in middle‐ and low‐income countries. Additionally, OS might result in ovarian hyperstimulation syndrome (OHSS), especially in women with ovulatory dysfunction secondary to hyperandrogenism. Another consideration is that standard OS protocols require daily injections, causing pain and being a potential source of bleeding/infection; the effect of psychological distress should not be overlooked.…”
Section: Introductionmentioning
confidence: 99%